Аналіз просторового розподілу заряджених частинок, народжених у Xe–Xe зіткненнях при √SNN=5.44 TeВ з використанням моделі PYTHIA8 Angantyr і багатофазної транспортної моделі - Singh, R.; Bala, R.; Sambyal, S.S. (Publishing house "Academperiodika", 2023)
Transverse spherocity is an event structure variable which provide an effective way to disentangle the data into hard and soft components of the processes corresponding to events with small and large numbers of multiparton interactions (MPI), respectively. Recent experimental results in small systems from the LHC suggest the importance of the transverse spherocity variable in the classification of the events. In this contribution, we have studied the dynamics of identified particle production in Xe–Xe collisions at √SNN = 5.44 TeV using A Multi-Phase Transport Model (AMPT) and the recently developed Angantyr model, which is incorporated within PYTHIA8. A study of the transverse momentum spectra of the identified particles is presented for soft (isotropic) and hard (jet-like) events in different centrality intervals.